Heat-not-burn tobacco product use in Japan: its prevalence, predictors and perceived symptoms from exposure to secondhand heat-not-burn tobacco aerosol. Issue Volume 27:Issue e1(2018) (16th December 2017) - Tabuchi, Takahiro; Gallus, Silvano; Shinozaki, Tomohiro; Nakaya, Tomoki; Kunugita, Naoki; Colwell, Brian
Abstract : Objectives: A heat-not-burn (HNB) tobacco product, IQOS, was first launched in Japan and Italy as test markets and is currently in commerce in 30 countries. Using two data sources, we examined interest in HNB tobacco (IQOS, Ploom and glo), its prevalence, predictors of its use and symptoms from exposure to secondhand HNB tobacco aerosol in Japan, where HNB tobacco has been sold since 2014. Methods: Population interest in HNB tobacco was explored using Google search query data. Prevalence of HNB tobacco current use (ie, use in the previous 30 days) was calculated using a longitudinal internet survey of 8240 individuals (15–69 years old in 2015) followed up to 2017. Rates of perceived symptoms from exposure to exhaled aerosol of others' HNB tobacco were also calculated. Results: The largest internet search volume for IQOS occurred in April 2016 in the week after a popular national entertainment TV show introduced IQOS. For Ploom and glo, search volumes have remained limited since their launch. Prevalence of IQOS users increased from 0.3% in January–February 2015 to 0.6% in January–February 2016 and up to 3.6% in January–February 2017, while estimated rates of use of other HNB tobacco products remained low in 2017. Respondents who had seen the TV programme in 2016 were more likely to have used IQOS than those who had not seen it (10.3% vs 2.7%). Among never-smokers who had been exposed to secondhand HNB tobacco aerosol, nearly half reported at least one acute symptom, although these symptoms were not serious. Conclusions: A popular TV programme triggered IQOS diffusion in Japan. Extrapolating from survey results to the general population, around 3.1 million people currently use IQOS in Japan. Tobacco control organisations and governments should closely monitor HNB tobacco and consider how to regulate it.